Pengembangan Website SATUINBOX di PT. X - Nathaniel Valentino Robert; Andreas Widjaja (Journal of Smart Technology and Engineering, 2026)
The rapid growth of online businesses demands solutions for effective customer communication management. PT. X developed a ticket-based chat platform to facilitate communication management between sellers and customers. The purpose of this internship project is to develop the frontend of the website with a focus on implementing a responsive and functional UI/UX design and API integration. The method used is Agile Scrum with a daily sprint approach in software development. Data collection techniques were carried out through direct observation and interviews with the development team. During the internship, the intern was responsible for implementing the UI/UX design through page slicing and integrating the backend API using Next.js and TypeScript. Responsiveness testing was performed to ensure proper functionality across various devices. The results showed that the platform was successfully implemented with a responsive interface and features that function optimally, including API integration and performance optimization. The conclusion of this study is that the frontend development successfully improved the platform's performance and enhanced the user experience.